2012
DOI: 10.1161/circresaha.112.266585
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin 2-Containing Mitochondrial-Reticular Microdomains Direct Rapid Cardiomyocyte Bioenergetic Responses Via Interorganelle Ca 2+ Crosstalk

Abstract: Rationale Mitochondrial Ca2+ uptake is essential for the bioenergetic feedback response through stimulation of Krebs cycle dehydrogenases. Close association of mitochondria to the sarcoplasmic reticulum (SR) may explain efficient mitochondrial Ca2+ uptake despite low Ca2+ affinity of the mitochondrial Ca2+ uniporter. However, the existence of such mitochondrial Ca2+ microdomains and their functional role are presently unresolved. Mitofusin (Mfn) 1 and 2 mediate mitochondrial outer membrane fusion, while Mfn2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
315
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 299 publications
(351 citation statements)
references
References 53 publications
(125 reference statements)
18
315
3
1
Order By: Relevance
“…Loss of Mfn2 also delayed membrane depolarization in isolated cardiomyocytes from adult Mfn2 −/− mice, leading to the suggestion that Mfn2 may function to control mitochondrial permeability transition pore opening (Papanicolaou et al, 2011). Similarly, cardiac‐specific deletion of Mfn2 produced dissipation of mitochondrial membrane potential and elevated ROS production (Chen et al, 2012), whilst overexpression of Mfn2 was found to increase the percentage of cells containing elongated mitochondria, thereby reducing mitochondrial permeability transition pore opening and cell death after simulated ischaemia/reperfusion injury (Ong et al, 2010). It also appears that Mfn2 serves an essential role in maintaining mitochondrial coenzyme Q levels in mouse hearts, thereby promoting optimal function of the respiratory chain (Mourier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Mfn2 also delayed membrane depolarization in isolated cardiomyocytes from adult Mfn2 −/− mice, leading to the suggestion that Mfn2 may function to control mitochondrial permeability transition pore opening (Papanicolaou et al, 2011). Similarly, cardiac‐specific deletion of Mfn2 produced dissipation of mitochondrial membrane potential and elevated ROS production (Chen et al, 2012), whilst overexpression of Mfn2 was found to increase the percentage of cells containing elongated mitochondria, thereby reducing mitochondrial permeability transition pore opening and cell death after simulated ischaemia/reperfusion injury (Ong et al, 2010). It also appears that Mfn2 serves an essential role in maintaining mitochondrial coenzyme Q levels in mouse hearts, thereby promoting optimal function of the respiratory chain (Mourier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One would also expect direct or indirect contribution by mitochondria-jSR tethers that secure the organelles together. Cardiac ablation of mitofusin 2, a multifunctional OMM protein that has been proposed to be (41) or not to be (42, 43) a mitochondria-ER tether in non-muscle cells, causes a decrease in mitochondria-jSR associations and Ca 2ϩ transfer, suggesting a tethering role in cardiomyocytes (44). However, the -fold enrichment of EMRE in the SR versus mitochondrial fractions was not affected significantly by cardiac mitofusin 2 ablation (n ϭ 4 mice), suggesting that either EMRE recruitment to the mitochondria-jSR association did not require mitofusin 2 or alternative mechanism(s) compensated for its loss.…”
Section: Discussionmentioning
confidence: 99%
“…MCUKO mice were housed/maintained in NIH-NHLBI 1 and used in the Murphy (cardiomyocyte isolation) and Finkel (heart homogenates and membrane fractions) laboratories. The cardiac muscle-specific Mfn2KO (Mfn2 flox/flox, MYH6 Cre) mouse colony originated from Gerald Dorn (Washington University, St. Louis, MO) and was maintained as described (44).…”
Section: Methodsmentioning
confidence: 99%
“…57 Together with our collaborators, we proved the existence of this same Mfn2 tethering function between cardiomyocyte mitochondria and the SR, and demonstrated that the calcium microdomains formed by Mfn2 tethers are essential for rapid mitochondrial sensing of increased SR calcium release during the early phase of increased cardiac work (Figure 3). 20 Ablating the Mfn2 mitochondria-SR tether does not adversely affect the young adult mouse heart at rest, but the resulting distortion of the normal, privileged interorganelle calcium export and uptake delays the mitochondrial ATP response to acute stress. Others have suggested that Mfn2 is essential for calcium-stimulated opening of cardiomyocyte MPTPs, presumably also by tethering mitochondria to the SR. 58 Thus, Mfn2 appears to be a centrally positioned orchestrator of both homeostatic mitochondrial fusion and mitochondrion-SR calcium crosstalk, modulating mitochondrial ATP production according to changing physiological demand and facilitating cardiomyocyte death in response to non-lethal stress by inducing programmed necrosis.…”
Section: Heart Diseases Caused By Defective Mitochondrial Fusionmentioning
confidence: 99%